The mesothoracic wings of Afrotropical Scutelleridae (Hemiptera: Heteroptera): morphology and taxonomic significance - Czaja, Joanna (Zootaxa, 2013)
Mesothoracic wings have been examined and compared in 32 species representing 20 genera of Afrotropical Scutelleridae. Morphological characters of the corium are described. Three main types of mesothoracic wing venation patterns can be recognized. The taxonomic significance of forewing characters in Scutelleridae is briefly discussed.